ANALISIS SPEKTRAL PENGGUNAAN LAHAN MENGGUNAKAN CITRA LANDSAT 8 DI SUB DAS MIU KECAMATAN GUMBASA KABUPATEN SIGI - Khairussidqih, Sayid; Akhbar, Akhbar; Wahid, Abdul; Misrah, Misrah; Hamka, Hamka (Jurnal Warta Rimba, 2021)
The Miu sub-watershed has a strategic function in providing ground water. Various community activities around the Miu sub-watershed have made its condition increasingly degraded which is quite serious in terms of its ecological, economic and social functions. As an initial step to maintain conservation, it is necessary to do land use in the Miu sub-watershed. This study aims to determine the type of land use found in the Miu sub-watershed and to determine the type of composite tape that is good for interpreting land. This research was carried out by conducting a composite image which was then carried out by taking training samples (sampling) then conducting a guided classification (supervised classification) and checking in the field and the last step was to test the accuracy of image accuracy. From the results of Landsat 8 image classification using composite band 632 obtained 6 land use classes and composite band 654 and band 653 obtained 7 land use classes consisting of Primary Forest, Secondary Forest, Plantation, Shrub, Settlements, Open Land, and Water Bodies. Meanwhile, from the results of the accuracy test using the Confusion Matrix method, the security band 654 has the highest level of accuracy with a total accuracy value of 85%, compared to composite band 653 which has an accuracy value of 74% and band 632 has an accuracy of 63%.Keywords: Landsat 8 imagery, classification, use, Miu . sub-watershed